WOMEN PARTICIPATION IN COMMUNITY RADIO IN NIGERIA: TOWARDS MARGINALIZATION OR EXCLUSION? ANALYSIS OF SELECTED CAMPUS COMMUNITY RADIO STATIONS - Dunu, Ifeoma Vivian (European Scientific Journal, ESJ, 2015)
The development of community radio in many countries has significantly transformed the media landscapes and communication discourses, introducing and enabling the inclusion of marginalized sectors of the public in the public sphere. Given the recent foray of Nigeria in this new media, it becomes imperative to examine the extent this fledgling sector in the country is enabling as well as engendering the participation of women in public discourses of the various communities where these community radios are operational. This work used content analysis as the research methodology to determine the level of women inclusion in the development of programme content and their level of participation in the running and operations of these stations. The study sampled various community campus radios in South East Nigeria. The samples include Madonna University community campus radio Okija, University of Nigeria Lion Fm Nsukka, UNIZIK Fm Awka and Caritas Fm Enugu. It was found that the programme contents of these stations are tailored towards entertainment and are male- oriented in nature. The number of males working in these stations was proportionately higher than that of the females, thus corroborating the findings of earlier studies on women and the media which suggest that as yet, there is no significant shift in women’s participation in the media. However, the study argues that the disparity may be as a result of the dominant socio-cultural practices that still reflect within state ideological apparatus and also the alignment of these emerging stations to dominant male-centric practices in media terrain in Nigeria.